Construction Of Employee Performance: Implementation Of Good Manager And Good Atmosphere Work At Hotel Horison Ultima Seminyak Bali - Wijaya, Anak Agung Gede (CV. Creative Tugu Pena, 2024)
Good managers in every industry and work atmosphere are several factors that can influence employee performance in an industry. Both play an important role in the industry's goals, namely achieving good employee performance. The purpose of this research is to find out how work atmosphere and Good Manager influence employee performance. As a sample, 101 employees from the Horison Ulima Hotel Seminyak Bali Restaurant were selected. Multiple regression analysis was used. The test results show that Good Manager and work atmosphere have a significant influence on employee performance at the Horison Ulima Hotel Seminyak Bali Restaurant. This shows that these variables are worthy of inclusion in the research model. The correlation coefficient obtained is various, which shows the strong correlation between the model used in this research and employee performance at the Horison Ulima Hotel Seminyak Bali Restaurant, and the results show that the influence of work atmosphere and Good Manager is very large on employee performance at the Horison Ulima Hotel Seminyak Bali Restaurant. Keywords: Construction of Employee Performance, Good Manager, Good Atmosphere Work